Assessing the Diversity and Metabolic Potential of Psychrotolerant Arsenic-Metabolizing Microorganisms From a Subarctic Peatland Used for Treatment of Mining-Affected Waters by Culture-Dependent and -Independent Techniques - Ziegelhöfer, Aileen; Kujala, Katharina (Frontiers in Microbiology, 2021)
Arsenic contamination in water by natural causes or industrial activities is a major environmental concern, and treatment of contaminated waters is needed to protect water resources and minimize the risk for human health. In mining environments, treatment peatlands are used in the polishing phase of water treatment to remove arsenic (amongst other contaminants), and peat microorganisms play a crucial role in arsenic removal. The present study assessed culture-independent diversity obtained through metagenomic and metatranscriptomic sequencing and culture-dependent diversity obtained by isolating psychrotolerant arsenic-tolerant, arsenite-oxidizing and arsenate-respiring microorganisms from a peatland treating mine effluent waters of a gold mine in Finnish Lapland using a dilution-to-extinction technique. Low diversity enrichments obtained after several transfers were dominated by the genera Pseudomonas, Polaromonas, Aeromonas, Brevundimonas, Ancylobacter and Rhodoferax. Even though maximal growth and physiological activity (i.e. arsenite oxidation or arsenate reduction) were observed at temperatures between 20-28°C, most enrichments also showed substantial growth/activity at 2-5°C, indicating the successful enrichments of psychrotolerant microorganisms. After additional purification, eight arsenic-tolerant, five arsenite-oxidizing and three arsenate-respiring strains were obtained in pure culture and identified as Pseudomonas, Rhodococcus, Microbacterium and Cadophora. Some of the enriched and isolated genera are not known to metabolize arsenic, and valuable insights on arsenic turnover pathways may be gained by their further characterization. Comparison with phylogenetic and functional data from the metagenome indicated that the enriched and isolated strains did not belong to the most abundant genera, indicating that culture-dependent and -independent methods capture different fractions of the microbial community involved in arsenic turnover. Rare biosphere microorganisms that are present in low abundance often play an important role in ecosystem functioning, and the enriched/isolated strains might thus contribute substantially to arsenic turnover in the treatment peatland. Psychrotolerant pure cultures of arsenic-metabolizing microorganisms from peatlands are needed to close the knowledge gaps pertaining to microbial arsenic turnover in peatlands located in cold climate regions, and the isolates and enrichments obtained in this study are be a good starting point to establish model systems. Improved understanding of their metabolism could moreover lead to their use in in biotechnological applications intended for bioremediation of arsenic-contaminated waters.